Capital culturel numérique des enseignants et territoires apprenants. Analyses des ressources et des parcours d’appropriation du numérique par les enseignants dans des tiers lieux coopératifs - Didier Perret; Pascal Plantard (Recherches en Éducation)
The article proposes an analysis of the differentiation of the appropriation of digital resources by tea-chers. It is focusing on the transformative potential of digital pedagogical cooperatives (CPN) deployed in schools in Brittany. These third places are used for teacher support and training in the territory. This analysis is based on the ethnography of the first connected junior secondary school of Saint-Brieuc. The experiment was conducted between 2016 and 2020 in the Academy of Rennes as part of the e-fran-idea research project. The research was linked with the creation of the four CPN by the Bretagne academic region. Our team studied the operation. Relying in particular on data from the Côtes d'Armor and Morbihan CPNs, we discuss the stakes and the purposes of the creation of these third places in schools. The activities of human resources (CPN facilitators, resource persons, student-apprentices, etc.) are at the heart of our analysis, which refers to the notion of resource, defined as the “means avai-lable to an individual or group to carry out an action”. These means depend on the opportunities of-fered by the environment, especially in the field of education, and the ability of individuals to mobilize them.